(untitled) (Journal of actual problems of jurisprudence, 2018)
In the article on the basis of analysis of the semantic meaning of the terms "crime fighting" and "mechanism to crossing crime," concluded the acceptability of using among with terms "crime fighting" and the phrase " mechanism to crossing crime," which assign how to use the opportunity to affection of crime various tools and methods, and on their interrelation with each other, and also underline the successive course of their administration by way of, completely adequate as a crime as a whole and its certain types. Keywords: criminality, crime prevention, Mechanisms for combating crime, criminological prediction.